GAMBARAN KEPRIBADIAN MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK BEDAK TABUR PIXY DI INDONESIA - Kartika, Diana Ani; Hurriyati, Ratih; Razati, Girang (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - The purpose of this study is to see the descriptionof the level ofbrand personality,andpurchase decision in consumers of Pixy powder in Indonesia. Design/methodology/approachh - The design of this study was cross sectional method. This research uses descriptive approach with explanatory survey method. The nurses analysis unit is 130 people. Data collection using questionnaire. The analysis technique used is descriptive technique by using frequency distributionFindings - Based on the results of the research using descriptive analysis, the results obtained that brand personality in the high category, and purchase decision in the good category.Originality/value - The differences in this study located on an object research , time research , a measuring instrument , literature that used , the theory that is used and the results of the study.Aaker, J. L. (1997). Dimensions of brand personality. Journal of Marketing Research, 347.Al-rasyid, H. (1994). Teknik Penarikan Sampel dan Penyusunan Skala. Bandung: Universitas Padjajaran.Arora, S., Neha. (2016). Determinants of Customer-based Brand Equity: A Study of Public and Private Banks. Global Business Review, 17(4), 905–920. Retrieved from http://doi.org/10.1177/0972150916645693Blackwell, R. D. (2005). Consumer Behaviour. Mason: Permissions Department.Buchari Alma. (2008). Mnajemen Pemasaran dan Pemasaran Jasa. Bandung: Alfabeta.Cravens, Piercy. (2013). Strategic Marketing (10th ed.) (10th ed). New York: Mc Graw Hil.Dirgantari, P. D. (2016). PERANAN BAURAN PEMASARAN JASA PENDIDIKAN TERHADAP UPAYA MENINGKATKAN EKUITAS MEREK BERBASIS PELANGGAN PERGURUAN TINGGI (STUDI PADA PERGURUAN TINGGI DI JAWA BARAT). Jurnal Pendidikan Manajemen Bisnis, 11, 22–31.Guthrie, M., Hye-shin, K., Jaehee, J. (2007). The effects of facial image andcosmetic usage on perceptions ofbrand personality. Journal of Fashion Marketing and Management, 12(2), 164–181. http://doi.org/10.1108/13612020810874863Hawkins, D. I. (2010). Building Marketing Strategy Consumer Behavior.Heding, T., Knudtzen, C. F., Bjerre, M. (2009). Brand Management.Hegner, S. M., Jevons, C., Hegner, S. M., Jevons, C. (2016). Brand trust : a cross-national validation in Germany , India , and South Africa. http://doi.org/10.1108/JPBM-02-2015-0814Karjaluoto, H., Munnukka, J., Salmi, M. (2016). Article information : Journal of Service Theory and Practice, 26(1).Kartajaya, H. (2010). Perjalanan Pemikiran Konsep Pemasaran Hermawan Kertajaya. Jakarta: Penerbit Erlangga.Keller, K. L. (2013). Strategic Brand Management (4th ed.). England: Pearson Education Inc. Retrieved from http://doi.org/10.2307/1252315Keller, K. L., Kotler, P. (2016). Marketing Management (15e ed.). England: Pearson Education Limited.Kotler, P., Keller, K., Brady, M., Goodman, M., Hansen, T. (2012). Marketing management. England: Pearson Education Limited.Kotler, P., Keller, K. L. (n.d.). Marketing Management.Kwong, M. Z., Candinegara, I. (2014). elationship between Brand Experience , Brand Personality , Consumer Satisfaction , and Consumer Loyalty of DSSMF Brand. iBuss Management, 2(2), 89–98.Laios, L. G., Moschuris, S. J. (2015). The influence of enterprise type on the purchasing decision process. International Journal of Operations Production Management.Lamb, C. W., Hair, J. F. (2011). Marketing.Malhotra, N. K. (2010). Marketing Research (6th ed.). United States of America.Mulyadi, H., Saktiawati, D. (2008). Pengaruh Brand Personality terhadap Loyalitas Pelanggan Sampo Sunsilk. Jurnal Pendidikan Manajemen Bisnis, 7.Noel, H. (2009). Consumer behaviour. Switzerland: AVA Publishing SA.Orozoco-Gomez, M., Toldos-Romeo Ma, M. de l P. (2015). Brand personality and purchase intention, 27(5), 462–467. http://doi.org/10.1108/EBR-03-2013-0046Peter, J. P., Jerry, C. O. (2008). Consumer Behaviour perilaku konsumen dan strtegi pemasaran. Jakarta: Erlangga.Rampl, L. V., Kenning, P. (2014). Employer brand trust and affect : linking brand personality to employer brand attractiveness. http://doi.org/http://doi.org/10.1108/EJM-02-2012-0113Ratih, H., Irna, W. (2008). pengaruh pemasaran eksperiensial terhadp retensi pelanggan pada pengunjung resort spa kampung sampireun garut. Jurnal Pendidikan Manajemen Bisnis, 7, 1–19.Razati, G., Ruhimat, R. (2008). pengaruh sales promotion terhadap keputusan pengguna kartu kredit bni. Pendidikan Manajemen Bisnis, 7.Sangadji, E. M., Sopiah. (2013). Perilaku Konsumen Pendekatan Praktis Disertai Himpunan Jurnal Penelitan. Yogyakarta: Andi offset.Schiffman, L. ., Kanuk, L. L. (2007). Consumer Behaviour. New Jersey: Pearson Prestice Hall.Solomon, M. R., Bamossy, G., Askegaard, S., Hogg, M. K. (2013). Consumer Behaviour.Sugiyono. (2010). Metode Penelitian Bisnis. Bandung: Alfabetha.Suharno. (2010). Marketing in Practice (edisi pert). Yogyakarta: Graha Ilmu.Surakhmad, W. (2004). Pengantar Penelitian Ilmiah Dasar Metode Teknik. Bandung: Tarsito.Utama, D. H., Amelia, F. (2009). ENGARUH ATRIBUT PRODUK TERHADAP KEPUASAN PELANGGAN PRODUK TEH CELUP SOSRO DAN 2 TANG (Survei Pada Pelanggan Teh Celup di Griya Pahlawan dan Giant Pasteur Bandung). Urnal Pendidikan Manajemen Bisnis, 8(30-40).Yin, C., Mansori, S. (2016). Factor that influences consumers ’ brand loyalty towards cosmetic products. Journal of Marketing Management and Customer Behavior, 1, 12–29.